2002
DOI: 10.1139/s02-036
|View full text |Cite
|
Sign up to set email alerts
|

A study of aerobic digester performance with the use of methanol for biological nutrient removal in a full-scale sequencing batch reactor

Abstract: The primary goal of this research was to determine whether the use of methanol in a full-scale sequencing batch reactor (SBR) affected the subsequent aerobic sludge digester performance. The methanol injection into an experimental SBR resulted in a significant increase in the solids level in the SBR, increased wasting into the digesters, and a lower sludge age. When the methanol dosage in the SBR was 81 L/d, the dissolved oxygen level in the subsequent aerobic digesters became inadequate for proper digestion. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2008
2008
2011
2011

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 5 publications
1
2
0
Order By: Relevance
“…In this study, 40 to 68% of suspended solids was degraded under different experimental conditions, which is consistent with observations made by other researchers (Mason et al, 1987;Koh et al, 2002;Novak et al, 2003), but was higher (three to six times) than the control used in these experiments. The solids-reduction rate is higher or equivalent to solids reduction typically observed in large-scale, conventional aerobic digestion.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…In this study, 40 to 68% of suspended solids was degraded under different experimental conditions, which is consistent with observations made by other researchers (Mason et al, 1987;Koh et al, 2002;Novak et al, 2003), but was higher (three to six times) than the control used in these experiments. The solids-reduction rate is higher or equivalent to solids reduction typically observed in large-scale, conventional aerobic digestion.…”
Section: Resultssupporting
confidence: 93%
“…Several authors have studied total-and volatile-suspended-solids (VSS) reduction in aerobic digesters using different configurations (batch mesophilic, semicontinous, thermophilic, sludge pretreatment through chemical, or enzyme methods). They found that degradation ranged from 50 to 80% VSS reduction (Mason et al, 1987;Koh et al, 2002;Li et al, 2003;Novak et al, 2003;Barbusinski and Filipek, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Several authors have studied the total and volatile suspended solids (VSS) reduction in aerobic digesters employing different process configurations (batch mesophilic, semi-continous, thermophilic, sludge pre-treatment through chemical or enzyme methods), and the degradation varied in the range of 50-80% VSS reduction [39][40][41][42]. The degradation of sludge solids mainly depends on solids retention time (SRT), solids concentration, microbial community and operating conditions [e.g., dissolved oxygen (DO), temperature and pH].…”
Section: Green Biotechnology To Improve Sludge (Aerobic and Anaerobicmentioning
confidence: 99%